Divine designation in the use of the Bible: The quest for an "all-powerful God" (the omnipotence of God) in a pastoral ministry of human empowerment - Louw, D. J. (HTS teologiese studies, 2020)
In our exposure to weakness, vulnerability, loss, anguish and different forms of impairment, the following pastoral theological questions arises: What is meant by divine almightiness within the human need for spiritual strength, empowerment, encouragement and well-being? The epithet of almightiness (omnipotence, pantokratōr) gave birth to fictitious and speculative associations, even fear and anxiety: The paralyzing fear of God Almighty – divine intoxicating and spiritual pathology. Instead of a pantokratōr-definition of God, a paraklēsis-infinition of God is proposed. This paradigm shift is based on the hermeneutical insight, namely, that the El Shadday of Yahweh is based on the respect in Jewish hermeneutics to render God not as a personified substance, but as an ‘operating verb’ – hjh. In the verbing of God, El Shadday points to encouragement, empowerment and a kind of pity and comfort based on the passio Dei.Contribution: How one perceives the power of God, determines the practice of Christian devotion and spirituality. Therefore, the emphasis on the notion of ‘God Almighty’ (omnipotence of God) and its link to the notion of the ‘weakness of God’ as exposed in the basic outline for a theology of the cross and as a source for hope in pastoral care and compassionate reaching out.